2012
DOI: 10.4007/annals.2012.176.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Coarse differentiation of quasi-isometries I: Spaces not quasi-isometric to Cayley graphs

Abstract: In this paper, we prove that certain spaces are not quasi-isometric to Cayley graphs of finitely generated groups. In particular, we answer a question of Woess and prove a conjecture of Diestel and Leader by showing that certain homogeneous graphs are not quasi-isometric to a Cayley graph of a finitely generated group. This paper is the first in a sequence of papers proving results announced in our 2007 article "Quasi-isometries and rigidity of solvable groups." In particular, this paper contains many steps in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 35 publications
1
94
0
Order By: Relevance
“…Eskin, Fisher and Whyte [4] recently established this conjecture. In this section we give a brief description of the DiestelLeader graphs (see or Woess [8] for more detailed descriptions).…”
Section: Diestel-leader Graphsmentioning
confidence: 87%
See 1 more Smart Citation
“…Eskin, Fisher and Whyte [4] recently established this conjecture. In this section we give a brief description of the DiestelLeader graphs (see or Woess [8] for more detailed descriptions).…”
Section: Diestel-leader Graphsmentioning
confidence: 87%
“…We choose X to be a Diestel-Leader graph DL(m, n) with m = n. These graphs have transitive groups of automorphisms, but Eskin, Fisher and Whyte [4] recently showed that they are not quasi-isometric to the Cayley graph of any group. The proof is completed by the observation that any surface which is a quasiconformal deformation of a regular cover of a closed orbifold is quasi-isometric to the Cayley graph of the deck transformation group.…”
Section: Introductionmentioning
confidence: 99%
“…The following result is stated in Eskin, Fisher and Whyte [4]. Its proof is completed by Dymarz in [2].…”
Section: Corollarymentioning
confidence: 87%
“…In this last section, we remove the condition that standard maps are only defined for a subset of relative large measure and align the translational part of the standard maps by adopting the procedure used to achieve this in Eskin, Fisher and Whyte [4].…”
Section: Patchingmentioning
confidence: 99%
See 1 more Smart Citation